The Dynamics of Low Income and Persistent Poverty Among U.S. Families - Hisnanick, John J. (Journal of Income Distribution®, 2007)
Are those in poverty likely to remain there or can they move out of this situationwithout help from other sources? Our understanding of those in or near poverty isprimarily based upon the analysis of either annual income or the income distributionfrom cross-sectional survey data. It has been argued in the literature that this type ofdata can be misleading when faced with questions pertaining to transitions in and outof poverty. Studies of the persistence of poverty should focus on individuals and theirfamilies, in conjunction with labor market situations, in order to provide an insightinto why the situation continues.Using the Survey of Income and Program Participation (SIPP) 1996 panel, it waspossible to investigate low-income dynamics and to model family incomes for theyears 1996-1999. This article provides a descriptive analysis that evaluates the lowincomedynamics of families and their exit and re-entry rates into low income. Italso investigates family income and poverty experiences based upon a componentsof-variance model that identifies permanent and transitory factors and provides insightinto low-income dynamics.